Investigating the effects of tourist engagement on satisfaction and loyalty. Issue 7 (11th June 2019) - Rasoolimanesh, S. Mostafa; Md Noor, Shuhaida; Schuberth, Florian; Jaafar, Mastura
ABSTRACT: This paper examine the concept of tourist engagement modeled as a second-order composite in the context of a heritage destination in Malaysia. In doing so, this study investigates the direct and indirect effects of tourist engagement through satisfaction on destination loyalty. Data was collected from tourists visiting Kinabalu National Park, Sabah, Malaysia. To investigate tourist engagement, this study employs confirmatory composite analysis in combination with the latest version of partial least squares- path modeling (PLS-PM) known as consistent partial least squares. The findings strongly support to model tourist engagement as a second-order composite and show a strong positive effect for tourist engagement on satisfaction and tourists' destination loyalty. Moreover, a strong indirect effect of tourist engagement on loyalty through satisfaction is revealed. This study has a number of practical implications for local authorities to sustain tourism development in the Kinabalu National Park.